ANALISIS WACANA KRITIS DALAM MEDIA SOSIAL INSTAGRAM TENTANG "WANITA KARIR" MODEL ANALISIS NORMAN FAIRCLOUGH - Adhi Kusuma; Muhammad Faruq Al Barqi; Ahmad Faisal; Bahrul Ulum (Communicative : Jurnal Dakwah dan Komunikasi, 2024)
This study aims to uncover the dynamics of discourse on "career women" on Instagram using the Critical Discourse Analysis (CDA) approach by Norman Fairclough. This approach consists of three dimensions of analysis: text (linguistic content), discursive practice (the process of text production and consumption), and social practice (broader social context). The findings reveal that the representation of career women on Instagram is complex, reflecting contradictions between narratives of women's empowerment and the pressures of traditional gender norms. Dominant narratives often portray career women as ideal multitaskers, but implicitly reinforce stereotypes about domestic responsibilities. This study concludes that social media discourse plays a significant role in shaping public perceptions of career women and highlights the need to construct more inclusive and unbiased narratives.